Cargasus the flying carabao - Alaurin, Edgardo Delgado Father, O.P (University of Santo Tomas Publishing House, 2020)
World-building is one very important convention of fantasy adventure and the author succeeds in construction a realm that is other-worldly yet also familiar, believable, and very close to home since the writer's sensibility is very Filipino.